2017
DOI: 10.1080/07420528.2017.1392551
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a dosing-time on toxicities induced by docetaxel, cisplatin and 5-fluorouracil in patients with oral squamous cell carcinoma; a cross-over pilot study

Abstract: Docetaxel, cisplatin plus fluorouracil (DCF) regimen is a useful chemotherapy, but is sometimes withdrawn due to severe adverse effects (AE). In this study, we examined whether the chronotherapy of DCF regimen could reduce the drugs-induced toxicities in clinical practice. Patients with oral squamous cell carcinoma were enrolled. Chemotherapy started at 10:30 (Morning-dosing) or 18:30 (Evening-dosing) for 5 days by a cross-over design. AE were assessed for 14 days after an initiation of each dosing. The grades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…For example, the study by Tsuchiya at al. on the influence of a dosing-time of docetaxel-, cisplatin- and 5-fluorouracile-induced toxicity in patients with OSCC, already demonstrated that a chronotherapy regimen (evening-dosing) might reduce severe adverse effects of these drugs in clinical practice [96]. However, large interpatient differences in circadian functions should be taken into account, and a significant variability in response to chronotherapy is expected.…”
Section: Relation Between Circadian Clock Gene and Cancer Developmentmentioning
confidence: 99%
“…For example, the study by Tsuchiya at al. on the influence of a dosing-time of docetaxel-, cisplatin- and 5-fluorouracile-induced toxicity in patients with OSCC, already demonstrated that a chronotherapy regimen (evening-dosing) might reduce severe adverse effects of these drugs in clinical practice [96]. However, large interpatient differences in circadian functions should be taken into account, and a significant variability in response to chronotherapy is expected.…”
Section: Relation Between Circadian Clock Gene and Cancer Developmentmentioning
confidence: 99%
“…Hence, they can be employed in chrono-chemotherapy for oral cancer treatment [52]. A recent study showed that chrono-chemotherapy of a combination of Docetaxel, Cisplatin, and Fluorouracil (DCF) helped to decrease the severity of the side effects of each of these drugs [53]; patients with OSCC had less vomiting, nausea, and neutropenia when treated with evening DCF dosing rather than with morning administration [53]. Thus, it seems promising that chrono-chemotherapy has the ability to reduce the severity/extent of the side effects of some chemotherapeutic drugs, which can be exploited as a novel therapeutic strategy in oral, head and neck cancer patients and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the circadian clock and circadian rhythm have been the research hotspots in life sciences and medicine (8,9,19), and its research results provide a solid foundation for chrono-chemotherapy. Meanwhile, the clinical practice also proves that chrono-chemotherapy for OSCC can reduce adverse reactions and increase the efficacy of drugs (16,17,25,26) and value for clinical application. However, there are still many issues that need further research: (I) although the current general evidence that chronochemotherapy for OSCC can reduce adverse drug reactions and increase drug efficacy, there is still a lack of large-scale randomized multi-center controlled clinical trial data, and there is also a lack of further stratified analysis data under the premise of large samples, such as the effects of factors like gender, age, different stages of the tumor, different genetic backgrounds and environment on the chronochemotherapeutic effect; (II) due to the different factors, such as rest-activity phases, living habits, dietary patterns and work of individuals, will affect the circadian rhythm, and even in the same individual the circadian rhythm may change in the different stages of the disease, the circadian rhythm may change.…”
Section: Treatment Of Chrono-chemotherapy Adverse Reactionmentioning
confidence: 99%
“…Also, the incidence rate of adverse reactions was significantly reduced (46.43% versus 76.19%), especially the incidence rate of grade III to IV severe adverse reactions is significantly reduced (7.14% versus 33.33%) (17). Tsuchiya et al (26) compared the adverse reactions of chrono-chemotherapy and conventional chemotherapy with a combination of docetaxel, cisplatin, and 5-FU for patients with stage III or IV OSCC. Docetaxel and cisplatin were delivered at night (rest phase) in the chrono-chemotherapy group, while docetaxel and cisplatin were delivered in the morning (active phase) in the conventional chemotherapy group.…”
Section: The Clinical Basis Of Chrono-chemotherapy For Osccmentioning
confidence: 99%